Multiplicity of Overvoltages during Arc Single Phase Earth Faults in 35 kV Electrical Grids - Zinoviy Bakhor; Andriy Yatseiko; Roman Ferensovych (Energy Engineering and Control Systems)
The arc overvoltages during the single phase to earth faults in electrical distribution grids of 6-35 kV are the object of the research in this paper. The development of 35 kV distribution electrical grids is accompanied by the construction of new overhead and cable power lines. It causes a change of the capacitive earth fault current in the grids and also affects the multiplicity of overvoltages in electrical distribution grids during the single phase to earth faults. The paper shows the research results of overvoltages during arc single phase to earth faults in 35 kV electrical grid with the different grounding modes of a grid neutral (an isolated neutral, a grounded neutral through an arc-quenching reactor, a grounded neutral through a resistor). The calculations were performed on the digital models of the investigation power grids. According to the research results, a mathematical model has been created, which allows obtaining the maximum expected multiplicity of overvoltages in 35 kV electrical grids during the single phase to earth faults. This allows making decisions about the optimal measures for the protection of an electrical equipment insulation taking into account expected values of overvoltages as early as at the stage of pre-design works for the development of such electrical grids.